PELATIHAN TEKNOLOGI SISTEM TERTANAM BAGI PEMUDA CIHERANG - Risnandar, Muhammad Aris; Andang, Asep; Permana, Prama (Jurnal Pengabdian Masyarakat Indonesia, 2023)
Appropriate Technology (TTG) is a technology that is expected to be able to answer people's needs in making their business easier. With optimal use of TTG, it is hoped that it will be able to increase people's income, increase the selling value of products, and even improve product quality so that an effective and efficient productive business will be created. The government has actually provided encouragement for the development of TTG, and has even provided regulations regarding the use of TTG through Minister of Home Affairs Regulation No. 20 of 2010 and the establishment of Appropriate Technology Service Posts (Posyantek) in each region. However, in reality, the use of TTG in society has not been able to provide optimal results. One form of technology that is easy to implement and has quite a large impact and is relatively cheap is the use of embedded system-based technology. This technology is contemporary technology that utilizes computer, microelectronics and telecommunications technology. The Ciherang Youth Association as a youth group in Ciherang Village, Cibeureum District, Tasikmalaya City explained that there are opportunities for using technology in their area, but due to limited knowledge and facilities, this cannot be realized. Based on these problems, the implementing team proposed a community service activity based on training and mentoring for the Cherang Youth Association which has the potential to develop TTG in the community. The methods that have been used in this activity are in line with the proposals that have been submitted, including: 1) socializing the role of TTG in society; 2) training and implementation of embedded system-based technology; and 3) provide guidance and direction in the future development of TTG.